Demystifying the fallacy of brain-drain in Nigeria's development discourse: engaging the burden and the contradictions (2016)
Desperate emigration among all categories of Nigerians is an indicator of challenging socioeconomic and development environment. As mass poverty, mediocrity and visionless leadership crept into the polity in the 1980s and became institutionalized over the years, it became apparent that striking a balance among the citizenry would translate to devising adjustment mechanisms, including emigration. This paper argues that although migration affects development in several ways, it is fallacious to locate underdevelopment of Nigeria in the ‘brain-drain syndrome’. Thus, while it is accepted that highly skilled Nigerians are among those leaving the country, a far higher number of this same category of people residing in the country are unemployed. At best, such migration is developmental given that it reduces the army of the-economically-disengaged. Hence, poor governance, gender inequity, ethnicity, illiteracy, HIV/AIDS, terrorism and youth restiveness individually and collectively have greater implications for attainment of sustainable development by Nigeria